Prudence, Well-being and Sport - Andrew Bloodworth (Sport, Ethics and Philosophy, 2014)
Participation in sport, in particular intensive elite sport may be associated with shorter and longer term risks to health. Elite sport participation might also be associated with a narrow focus, to the detriment of developing in other ways, perhaps with regard to friendships or education. This paper explores the issues surrounding prudence and sport. It begins by examining two central aspects of the rationale for prudential engagement with sport and physical activity. (1) The contention that each stage of life counts equally in assessing well-being over a life; and (2) The need to detach from present concerns and commitments to maintain a range of options from which to pursue well-being in the future. These aspects of a prudential athletic lifestyle, along with the contention that prudence can be defended in terms of rationality are explored and challenged. These challenges are not found to be persuasive in terms of abandoning altogether the notion that a prudent engagement with sports and physical activity is a rational one. Stronger objections to the current understanding of the recommendations of prudence are found upon examination of Griffin’s theory of well-being. The fact that values on a list such as Griffin’s might be realised in multiple ways casts doubt on the contention that certain choices now will necessarily risk future well-being. Second, Griffin’s understanding of the relationship between health and well-being (health as a means to well-being) throws into doubt common interpretations of harms to health and their impact upon well-being. Accepting that there are multiple ways in which to fulfil those values constitutive of well-being, and that health is a purely instrumental good, offers a strong challenge to construing certain choices in the sports and exercise domain as imprudent and ultimately detrimental to well-being.